2002
DOI: 10.1080/03079450120106633
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an in ovo infection with a Dutch avian leukosis virus subgroup J isolate on the growth and immunological performance of SPF broiler chickens

Abstract: The effect of an in ovo infection with a Dutch isolate of avian leukosis virus subgroup J (ALV-J) on the growth of specific pathogen free (SPF) broiler chickens was analysed. During this study, possible immune suppressive effects of ALV-J were assessed by measuring delayed-type hypersensitivity with keyhole limpet haemocyanin (KLH), natural killer (NK) cell activity, the production of radicals of nitric oxide (NO) by macrophages, humoral immune response against Newcastle and infectious bursal disease vaccine v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…The data on RAV-2 and RAV-49 document that within both subgroups, ALV-B and ALV-C, differences in pathogenicity exist between individual viral strains and indicate that both wasting and the lymphoid tissue alteration may be induced independently. This conclusion is also supported by recently published data on ALV-J pathogenicity for in ovo infected chickens, in which significant growth suppression was not accompanied by alteration of immune responsiveness (Landman et al, 2002). Endogenous avian retroviral sequences that participated in ALV-J formation (Bai et al, 1995) represent a potential source of genetic material for the occurrence of recombinants accommodating new pathogenic properties dif- Figure 1.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The data on RAV-2 and RAV-49 document that within both subgroups, ALV-B and ALV-C, differences in pathogenicity exist between individual viral strains and indicate that both wasting and the lymphoid tissue alteration may be induced independently. This conclusion is also supported by recently published data on ALV-J pathogenicity for in ovo infected chickens, in which significant growth suppression was not accompanied by alteration of immune responsiveness (Landman et al, 2002). Endogenous avian retroviral sequences that participated in ALV-J formation (Bai et al, 1995) represent a potential source of genetic material for the occurrence of recombinants accommodating new pathogenic properties dif- Figure 1.…”
Section: Discussionsupporting
confidence: 73%
“…The main clinical sign of the wasting syndrome is progressive weight loss, which is accompanied by metabolic and hormonal disorders, depletion of lymphatic organs and immunosuppression, and in some cases also by osteopetrosis, anaemia and, occasionally, diarrhoea (Meyers et al, 1976;Smith & Van Eldik, 1978;Price & Smith, 1982;Rupp et al, 1982;Fadly et al, 1982;Landman et al, 2002;reviewed in Svoboda et al, 2003). Carter & Smith (1984) pointed out a specific pathogenic effect of subgroup C viruses, characterized by stunting, hypothyroidism, hyperinsulinaemia, alteration of lipid metabolism and lymphoblastoid infiltration of the liver, thyroid and pancreas.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of infected chickens can reflect viral replication in vivo (12,32). As shown in Table 1, the SPF layers and commercial broilers infected with rHLJ09SH01 showed a higher infection proportion than the chickens infected with rHLJ09SH01A205 within the first 2 weeks after hatching.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the failure to detect neutralizing antibodies for either virus in these chickens 7 weeks after hatching was not unexpected. Cloacal swabs from the hatched chickens were tested for the p27 antigen to evaluate the success of the ALV-J infection process; generally, the proportion of infected chickens reflects the replication of virus in vivo (12,32). The cloacal swabs collected 1, 6, and 15 days after hatching showed that infection with rHLJ09SH01 resulted in a higher proportion of p27 ELISApositive SPF layers and commercial broilers than infection with rHLJ09SH01A205, indicating that the 205-nucleotide deletion confers a replication advantage on ALV-J in vivo (Table 1).…”
Section: Figmentioning
confidence: 99%
“…Since its discovery in the United Kingdom, a variety of ALV-J strains in diverse geographical areas, including North America, Europe, East Asia, Australia, and the Middle East, have been characterized (6)(7)(8)(9)(10)(11). It is believed that these isolates derive from a single common ancestor and are not the result of independent recombination events (6).…”
mentioning
confidence: 99%